2002
DOI: 10.1080/10428190290016971
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epstein-Barr Virus DNA Load Monitoring in Prevention and Early Detection of Post-transplant Lymphoproliferative Disease

Abstract: Posttransplant lymphoproliferative disease (PTLD) is a severe and life-threatening complication after stem cell or solid-organ transplantation, virtually always associated with presence of Epstein-Barr virus (EBV) in the proliferating cells. PTLD is probably caused by the iatrogenically impaired T-cell response allowing outgrowth of EBV-positive B-cells. Quantitative EBV DNA load monitoring is a minimally invasive technique increasingly recognized as a valuable tool in posttransplant patient management. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 76 publications
1
80
1
3
Order By: Relevance
“…35 The current study reports a cumulative incidence of EBV reactivation of 15 and 21% at 6 months and 3 years after allo-HSCT, respectively, but none of the patient experienced EBV-related LPD signs or mortality. In this series, the absence of EBV-related severe complications is likely due to both the strict policy of EBV monitoring during the first months after allo-HSCT and the systematic use of pre-emptive rituximab in those patients experiencing a viral load 41000 copies/10 5 cells as recently described by Blaes et al 21 Indeed, numerous studies 17,18,20,22,[36][37][38] already showed that EBV viral load monitoring in the peripheral blood may be of value in high-risk populations after allo-HSCT. Recent evidence-based guidelines recommended weekly screening of EBV-DNA for at least 3 months in high-risk allo-HSCT recipients.…”
Section: Discussionmentioning
confidence: 95%
“…35 The current study reports a cumulative incidence of EBV reactivation of 15 and 21% at 6 months and 3 years after allo-HSCT, respectively, but none of the patient experienced EBV-related LPD signs or mortality. In this series, the absence of EBV-related severe complications is likely due to both the strict policy of EBV monitoring during the first months after allo-HSCT and the systematic use of pre-emptive rituximab in those patients experiencing a viral load 41000 copies/10 5 cells as recently described by Blaes et al 21 Indeed, numerous studies 17,18,20,22,[36][37][38] already showed that EBV viral load monitoring in the peripheral blood may be of value in high-risk populations after allo-HSCT. Recent evidence-based guidelines recommended weekly screening of EBV-DNA for at least 3 months in high-risk allo-HSCT recipients.…”
Section: Discussionmentioning
confidence: 95%
“…It is documented that elevated EBV DNA is a common phenomenon for HIV patients, reflecting rather insufficient immune-mediated control of EBV replication then underlying lymphoproliferative disease (Stevens et al, 2002a). In organ transplant recipients, EBV DNA monitoring allows early diagnosis of threatening posttransplant lymphoproliferative disease, which is preceded by high viral load several months before outbreak of disease (Stevens et al, 2001a;Stevens et al, 2002b). Therefore, clinical relevance of increased EBV DNA levels in different groups of immunocompromised patients may be different.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the shedding of infectious virions into the blood is a major component of CMV disease, but does not play a significant role in PTLD. 2,14,15 Type III latency (the same found in lymphoblastoid B-cell lines) predominates in most PTLD, although multiple latency patterns may be present within a single lesion with lytic replication in a fraction of cells. 14 This heterogeneity is likely to further complicate quantitative PCR approaches.…”
Section: Potential Shortcomings Of the Preemptive Pcr Approachmentioning
confidence: 99%
“…An excellent review of assay methods used in solid organ transplant and HSCT recipients was recently published. 14 We will focus solely on PCR assays evaluated in HSCT recipients, as the pathogenesis, timing and course of PTLD differ significantly between these patients and solid-organ transplant recipients. 2,15 Sensitive PCR assays can detect low levels of circulating EBV in many healthy individuals, limiting the predictive ability of qualitative assays.…”
Section: Risk Factors For Ptldmentioning
confidence: 99%